2013
DOI: 10.1111/nph.12289
|View full text |Cite
|
Sign up to set email alerts
|

High‐copy sequences reveal distinct evolution of the rye B chromosome

Abstract: SummaryB chromosomes (Bs) are supernumerary chromosomes that vary in number among individuals of the same species. Because of their dispensable nature, their non-Mendelian inheritance and their origin from A chromosomes (As), one might assume that Bs followed a different evolutionary pathway from As, this being reflected in differences in their high-copy DNA constitution. We provide detailed insight into the composition and distribution of rye (Secale cereale) B-located high-copy sequences.A-and B-specific hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 62 publications
5
93
0
Order By: Relevance
“…The most widely accepted view is that they are derived from the A chromosome complement [Jamilena et al, 1995a;Martis et al, 2012]. In Secale cereale , although the B chromosomes contained a similar proportion of repeats as the A chromosomes, the 2 differed significantly in composition due to an additional massive accumulation of B-specific satellite repeats [Klemme et al, 2013]. Not all B-enriched sequences are unique to the B, suggesting that B originated from A chromosomes.…”
Section: Chromosome-specific and Interstitial Satellite Dnasmentioning
confidence: 99%
See 2 more Smart Citations
“…The most widely accepted view is that they are derived from the A chromosome complement [Jamilena et al, 1995a;Martis et al, 2012]. In Secale cereale , although the B chromosomes contained a similar proportion of repeats as the A chromosomes, the 2 differed significantly in composition due to an additional massive accumulation of B-specific satellite repeats [Klemme et al, 2013]. Not all B-enriched sequences are unique to the B, suggesting that B originated from A chromosomes.…”
Section: Chromosome-specific and Interstitial Satellite Dnasmentioning
confidence: 99%
“…Together with the satellite DNAs found in plant sex chromosomes, this is an unusual case of a satellite DNA family exclusive to a single chromosome pair of the karyotype of one species. In addition to these cases of chromosomespecific satellite DNAs, it has been reported that satellite DNAs also accumulate within B chromosomes [Klemme et al, 2013]. Supernumerary chromosomes or B chromosomes are dispensable genetic material found both in plant and animals [Camacho, 2005].…”
Section: Chromosome-specific and Interstitial Satellite Dnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of Bs in Cestrum is similar, but differences in composition and size of heterochromatin blocks suggest that they have been originated independently from each other (Fregonezi et al 2004). This hypothesis needs to be verified, since the variation in heterochromatin observed in the Bs may be also explained by their rapid evolution (Houben et al 2014), which make them subject of structural changes such as accumulation of repetitive DNAs (Lamb et al 2007;Klemme et al 2013). …”
Section: Physical Mapping Of Ribosomal Rna Genes In the Bsmentioning
confidence: 99%
“…Large insertions of plastid and mitochondrial DNA sequences are sometimes detected in plant Bs (Martis et al ., 2012; Klemme et al ., 2013; Ruban et al ., 2014), although none have been found in P. autumnale Bs. Bs frequently share repeat families with the A complement, but also accumulate B‐specific families (Langdon et al ., 2000; Dhar et al ., 2002; Marques et al ., 2012; Martis et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%